Incidence and Associated Risk Factors for Lactic Acidosis Induced by Linezolid Therapy in a Case–Control Study in Patients Older Than 85 Years - Liu, Tingting; Hu, Chao; Wu, Jionghe; Liu, Miao; Que, Yifan; Wang, Jiang; Fang, Xiangqun; Xu, Guogang; Li, Hongxia (Frontiers in Medicine, 2021)
Background: Serum lactic acid is considered a prognostic indicator in critically ill patients. However, studies on linezolid-induced lactic acidosis (LILA) are still limited. Individuals older than 85 years old (very elderly) have limited capacity for organ compensation, and LILA data from these patients are lacking. In this study, we evaluated the risk factors for LILA in patients older than 85 years and established a risk prediction model for geriatric practice. Methods: In this retrospective cohort study, blood gas analysis data and arterial lactate levels were monitored in patients older than 85 years during the use of teicoplanin or linezolid. After propensity score matching (PSM) analyses, we compared the incidence of lactic acidosis between the teicoplanin and linezolid therapy groups and identified the risk factors of LILA. Results: The incidence of lactic acidosis was found to be much lower in the group receiving teicoplanin than those receiving linezolid therapy (0% vs 35.7%; p<0.0001). A duration of linezolid therapy ≥9 days (odds ratio (OR), 3.541; 95% CI, 1.161-10.793; p=0.026), an arterial blood glucose level ≥8 mmol/L (OR, 4.548; 95% CI, 1.507-13.725; p=0.007) and a high sequential organ failure assessment (SOFA) score (OR, 1.429; 95% CI, 1.213-1.685; p<0.0001) were risk factors for LILA. The constructed risk model could be used for prediction of LILA (area under the curve, 0.849; specificity, 65.1%; sensitivity, 91.4%, with a negative predictive value of 93.2% and a positive predictive value of 59.3%). Conclusions: LILA can occur in patients older than 85 years old after a relatively shorter duration of linezolid therapy. Therefore, close monitoring of blood gas and arterial lactate levels during linezolid therapy in the very elderly population is necessary.